PERANCANGAN ALAT PEMECAH KEDELAI YANG ERGONOMIS DENGAN PENDEKATAN INTEGRASI MODEL KANO & QUALITY FUNCTION DEPLOYMENT - Asih, Endang Widuri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Operator work facility is one of the factors which influence work performance in a system. Good work facility must be comfortable for the operator. Operator work facility in a soya curd industry is a soya breaking tool. This tool doesn’t fulfill the standardized concept of ergonomy and user satisfaction. In this paper we are going to discuss operator work facility improvement; that is designing of an ergonomic soya breaking tool which is ideal and needed by the users. In the designing of the soya breaking tool, Kano and QFD models are intergratedly used. The result of the need analysis, we found twelve atributes. From the twelve attributes, after we processed by using Kano model about operator sa-tisfaction, applied in the House of Quality (HOQ), we found that there were five attributes in performance 1 and Basic factor. Those attributes were; the tool was easily maintained, the production process is fast, the tool is not tiring, the tool is save, and design is justified with the work position. To improve the quality of soya breaking tool by using Kano and QFD models, there are two primary factors. First, the tool size used Anthropometry, se-cond, the tool is operated by using feet.